2021
DOI: 10.3389/fpsyg.2021.789883
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to COVID-19 Scams: The Roles of Age, Individual Difference Measures, and Scam-Related Perceptions

Abstract: As the COVID-19 pandemic was unfolding, a surge in scams was registered across the globe. While COVID-19 poses higher health risks for older adults, it is unknown whether older adults are also facing higher financial risks as a result of COVID-19 scams. Here, we examined age differences in vulnerability to COVID-19 scams and individual difference measures (such as impulsivity, ad skepticism, and past experiences with fraud) that might help explain them. A lifespan sample (M = 48.03, SD = 18.56) of sixty-eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…41 Decisionmaking, in particular scam susceptibility, are complex behaviors that involve integration and coordination of diverse cognitive, affective, and socioemotional resources that rely on distributed neural networks. 5,14,42,43 We conceptualize that the presence of macroscopic infarcts (as well as AD pathology) impacts these brain networks and degrades specific abilities that may heighten vulnerability to scams. Neuroimaging studies have identified several interacting brain regions within, or highly connected to the frontal lobe, a brain region particularly vulnerable to infarcts (strokes) and β-amyloid pathology in early stages of AD, are likely involved in eco- nomic decision-making and socioemotional abilities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…41 Decisionmaking, in particular scam susceptibility, are complex behaviors that involve integration and coordination of diverse cognitive, affective, and socioemotional resources that rely on distributed neural networks. 5,14,42,43 We conceptualize that the presence of macroscopic infarcts (as well as AD pathology) impacts these brain networks and degrades specific abilities that may heighten vulnerability to scams. Neuroimaging studies have identified several interacting brain regions within, or highly connected to the frontal lobe, a brain region particularly vulnerable to infarcts (strokes) and β-amyloid pathology in early stages of AD, are likely involved in eco- nomic decision-making and socioemotional abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we have shown that the functional impact of various pathologies depends on combination, severity, and pattern of accumulation of brain pathologies . Decision-making, in particular scam susceptibility, are complex behaviors that involve integration and coordination of diverse cognitive, affective, and socioemotional resources that rely on distributed neural networks . We conceptualize that the presence of macroscopic infarcts (as well as AD pathology) impacts these brain networks and degrades specific abilities that may heighten vulnerability to scams.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this study was not designed to be COVID-19 specific, we would be remiss not to acknowledge the ways in which COVID-19 may have changed online behaviors and influenced responses to our research questions. The COVID-19 pandemic resulted in significant changes to how much of the world operated and saw a rise and evolution in both internet use (Feldmann et al 2020) and online harms (Nolte et al 2021;Wood, Hengerer, and Hanoch 2022;Stock 2020). Most countries enacted lockdowns of varying severity and length.…”
Section: Discussionmentioning
confidence: 99%